Are body esteem, eating attitudes, pressure to be thin, body mass index and training age related in rhythmic gymnastics athletes? - Trevithick, B.; Stuelcken, M.; Mellifont, R.; Sayers, M. (Science of Gymnastics Journal, 2018)
Rhythmic gymnastics athletes participate and compete from a very young and critical period of their lives, as childhood and adolescence. Purpose of the present study was to examine the relationship between body esteem, eating attitudes, perceived pressure to be thin by coaches, parents and friends, Body Mass Index (BMI) and training age in rhythmic gymnastics athletes. Eighty-three rhythmic gymnastics athletes participated (49 current and 34 former). They completed self reported questionnaires assessing demographic and personal characteristics, body esteem, global eating attitudes, and pressure to be thin by coaches, parents and friends. The results revealed that body esteem was predicted significantly by pressure to be thin by parents, BMI and training age. Also, former athletes had more positive body esteem and eating attitudes than current athletes, and current athletes felt more pressure to be thin by their parents, than former athletes. The results of the present study led to several suggestions for further studies.